1995
DOI: 10.1038/bjc.1995.323
|View full text |Cite
|
Sign up to set email alerts
|

Tumour vasculature - a potential therapeutic target

Abstract: Summary The tumour vasculature is vital for the establishment, growth and metastasis of solid tumours. Its physiological properties limit the effectiveness of conventional anti-cancer strategies. Therapeutic approaches directed at the tumour vasculature are reviewed, suggesting the potential of anti-angiogenesis and the targeting of vascular proliferation antigens as cancer treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 122 publications
0
47
0
Order By: Relevance
“…Tumour angiogenesis can be inhibited by blocking more than one of these steps. Prevention of tumour angiogenesis involves inhibition of synthesis of angiogenic factors and blocking of their receptors (Barillie et al, 1995;O'Brien and Harris, 1995). Until now there have been few reports regarding the inhibition of expression and production of angiogenic factors (Sidky and Borden, 1987;Singh et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Tumour angiogenesis can be inhibited by blocking more than one of these steps. Prevention of tumour angiogenesis involves inhibition of synthesis of angiogenic factors and blocking of their receptors (Barillie et al, 1995;O'Brien and Harris, 1995). Until now there have been few reports regarding the inhibition of expression and production of angiogenic factors (Sidky and Borden, 1987;Singh et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The tumour vasculature is a promising new target in cancer therapy, and a number of antitumour agents have been identified that either inhibit tumour angiogenesis (Baillie et al, 1995) or destroy the tumour's existing blood supply (Baguley, 2001). Tumour necrosis factor (TNF), a pleiotropic cytokine that is produced mainly by activated monocytes/macrophages, neutrophils, and T cells (Balkwill, 1989), is thought to exert its antitumour effect mainly through an antivascular mechanism.…”
mentioning
confidence: 99%
“…Furthermore, chemotherapy that induces vessel wall or endothelial cell death results in loss of vascular integrity, platelet aggregation and vascular occlusion, denying oxygen delivery and precipitating tumor cell death downstream (23). The identification of molecular markers that differentiate newly formed capillaries from their mature counterparts (24,25) has paved the way for targeted delivery of cytotoxic agents to the tumor vasculature (26). The α V ÎČ 3 integrin is one of the most specific of these unique markers.…”
Section: Discussionmentioning
confidence: 99%